2008
DOI: 10.2137/145960609788066816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine and iron diet supplementations on growth performance, carcass characteristics and blood metabolites in fattening pigs

Abstract: The aim of this study was to evaluate the effect of dietary L-carnitine supplementation either with or without extra Fe supplementation from Fe-amino acid (Fe-AA) complex on body weight gain, feed conversion, carcass characteristics and blood metabolite concentrations in fattening pigs. The study was carried out with 75 fatteners (30-100 kg body weight), divided into three groups, of 25 pigs each. The control group was given a basal diet that contained 85 mg/kg of Fe from premix. A L-carnitine group was given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Results of the current studies showed similar improvement. Adding L-carnitine to finishing diets had no appreciable effects on dressing percentage, which is similar to the findings of Pietruszka et al (2009), who reported similar dressing percentages when 0 or 100 mg/kg L-carnitine were added to finishing pig diets.…”
Section: Carcass Measurementssupporting
confidence: 87%
See 1 more Smart Citation
“…Results of the current studies showed similar improvement. Adding L-carnitine to finishing diets had no appreciable effects on dressing percentage, which is similar to the findings of Pietruszka et al (2009), who reported similar dressing percentages when 0 or 100 mg/kg L-carnitine were added to finishing pig diets.…”
Section: Carcass Measurementssupporting
confidence: 87%
“…Heo et al (2000b) reported that adding 500 mg/kg L-carnitine reduced lipid accretion. However, Pietruszka et al (2009) failed to detect an effect of 100 mg/kg of dietary L-carnitine on LM weight or area and the percentage lean.…”
Section: Carcass Measurementsmentioning
confidence: 92%
“…In accordance with previous works in pigs (Bunter et al, 2005;Estany et al, 2007), the concentration of plasma IGF-I was found to be not neutral with respect to fatness. However, contrarily to results here, IGF-I, as well as FE (Pietruszka et al, 2009), has been found to be primarily related to increased growth and lean content. Because circulating IGF-I displayed a marked nonlinear trend from shortly after weaning to peripuberty, and it is also easily influenced by recent feeding events (Therkildsen et al, 2004), its effect on fat content and composition may change across genetic types and measurement timepoints.…”
Section: Tablesupporting
confidence: 49%
“…Studies in chickens (Seo et al, 2008;Petrovič et al 2010) and pigs (Novotny et al, 2003;Pietruszka et al, 2009) did not show a consistent increase of iron concentrations in meat as a result of organic iron supplementation. The greatest increases, reported by Seo et al (2008), were as +34.5, +18.4 and +34.6 %, in breast, thigh and wing muscle, respectively.…”
Section: Iron Deposition In Tissues and Products Of Animal Originmentioning
confidence: 94%